Improved gastrointestinal profile with diroximel fumarate is associated with a positive impact on quality of life compared with dimethyl fumarate: results from the randomized, double-blind, phase III EVOLVE-MS-2 study. (March 2021) - Wundes, Annette; Wray, Sibyl; Gold, Ralf; Singer, Barry A.; Jasinska, Elzbieta; Ziemssen, Tjalf; de Seze, Jerome; Repovic, Pavle; Chen, Hailu; Hanna, Jerome; Messer, Jordan; Miller, Catherine; et al.
Background: Diroximel fumarate (DRF) is a novel oral fumarate approved for relapsing forms of multiple sclerosis (MS). DRF demonstrated significantly improved gastrointestinal (GI) tolerability versus dimethyl fumarate (DMF) with fewer days of Individual Gastrointestinal Symptom and Impact Scale (IGISIS) scores ⩾2, GI adverse events (AEs), and treatment discontinuations due to GI AEs. Our aim was to evaluate the impact of GI tolerability events on quality of life (QoL) for patients with relapsing–remitting MS who received DRF or DMF in EVOLVE-MS-2. Methods: A post hoc analysis was conducted in patients who were enrolled in the randomized, blinded, 5-week, EVOLVE-MS-2 [ClinicalTrials.gov identifier: NCT03093324] study of DRF versus DMF. Patients completed daily IGISIS and Global GISIS (GGISIS) eDiary questionnaires to assess GI symptom intensity and interference with daily activities and work. Results: In total, 504 patients (DRF, n = 253; DMF, n = 251) received study drug and 502 (DRF, n = 253; DMF, n = 249) completed at least one post-baseline questionnaire. With DRF, GI symptoms were less likely to interfere 'quite a bit' or 'extremely' with regular daily activities [IGISIS: DRF, 9.5% (24/253) versus DMF, 28.9% (72/249)] or work productivity [GGISIS: DRF, 6.1% (10/165) versus DMF, 11.3% (18/159)]. DRF-treated patients had fewer days with ⩾1 h of missed work (DRF, 43 days, n = 20 versus DMF, 88 days, n = 26). DMF-treated patients reported highest GI symptom severity and missed work at week 2–3 shortly after completing the titration period, which coincided with the majority of GI-related treatment discontinuations [58.3% (7/12)]. GI tolerability AEs [DRF, 34.8% (88/253); DMF, 48.2% (121/251)], concomitant symptomatic medication use [DRF, 19.3% (17/88) versus DMF, 30.6% (37/121)], and GI-related discontinuations (DRF, 0.8% versus DMF, 4.8%) were lower with DRF versus DMF. Conclusions: The improved GI tolerability with DRF translated into clinically meaningful benefits to QoL, as patients experienced less impact on daily life and work and required less concomitant symptomatic medication use. Trial registration: [ClinicalTrials.gov identifier: NCT03093324]